Penerapan Algoritma Boruvka Pada Jaringan Listrik : (Studi Kasus Pada Kelurahan Tanjung Pinggir Kecamatan Siantar Martoba) - Novita Sari Saragih; Mulyono Mulyono (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2023)
This research was conducted in Tanjung Pinggir, Siantar Martoba District to determine the optimization of electrical installations using the Boruvka algorithm to find a minimum spanning tree node with a minimum number of 3 consecutive nodes. Edges that do not form a circuit. Based on data obtained from PT. PLN (Persero) UP3 Pematangsiantar, then a picture of the installed network graph is obtained. The results obtained for the electrical installation diagram were obtained by using Python and the 2,591 meter Boruvka algorithm to obtain a minimum spanning tree. In this case, the electricity distribution cable is reduced by 41 meters compared to the previous total installation of 2,632 meters.